Respostas do plâncton e da qualidade da água sob ameaças frequentes em lagos tropicais: um estudo de caso na lagoa Carioca (médio Rio Doce, Minas Gerais) - Marina Isabela Bessa da Silva (2021)
The majority of freshwater ecosystems in the tropics have already faced disturbances caused by direct or indirect human actions, as eutrophication and exploitation of hydric resources to using water in agriculture or pasture, for example. Nowadays, those disturbances are becoming amplified with the increase of climate change effects, as changes in rain patterns, and the intensity of sunlight incident on the planet. Such modifications cause consequences in the metabolism and functioning of the lake. In this context, it is crucial the understanding of biogeochemical cycles alterations and plankton communities. Thus, this work aimed to: 1) investigate the response of planktonic communities through a mesocosms experiment with the addition of nutrients, allochthonous organic matter and shading, and the interaction of these additions in a tropical lake (Carioca Lake, Middle Rio Doce), surrounded by Atlantic forest; and 2) evaluate changes in different parameters of water quality of Carioca Lake after a considerable volume loss caused by recent changes in regional rain patterns. In mesocosms experiment, we observed responses in plankton composition after a few days of experiment, with alterations on structure and density of this community. The nutrients addition favored the dominance of phytoplankton opportunistic species, as Chlorella sp., and the organic matter addition provoked a substitution in dominance of Pseudanabaena catenata to Aphanocapsa elachista. In zooplankton, we observed the dominance substitution of Copepoda to Rotifera in all mesocosms, and the groups were associated with water transparency (diffuse attenuation coefficients of solar radiation) and bacterioplankton. On the other hand, the volume loss in the lake caused strong impacts in many of the observed parameters. The lake became less transparent and with higher nutrients concentrations in water column. We observed a significant increase in nitrogen concentration, essential nutrient in eutrophication process. The optical properties indicate that the lake darkening seems to occurred due to increasing on dissolved organic carbon concentration through the allochthonous organic matter input especially during summer, when the strong rains, common at this season, causes a massive water entrance, that also carries the organic material. Still, the rain events did not present a delimited frequency, and it was not enough to increase water levels that were lost by the lake during the dry season. This study presents the modifications in water quality and in structure and composition of planktonic community. The answers obtained in this work through simulation of eutrophication, land-use changes (that alters the quality and quantity of allochthonous organic matter in the system) and through observation on regional rainfall, can be extrapolated to development of aquatic environment conservation politics.